IMPLEMENTASI PROBLEM BASED LEARNING PADA PELAJARAN FIQIH MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS PESERTA DIDIK - Harun Kholidur Rosidi; Iswantir Iswantir; Rita Asnimar (Al Wildan: Jurnal Manajemen Pendidikan Islam, 2022)
Based on the results of daily tests on fiqh subjects, it shows that learning is less successful because it is still below the specified KKM, even though the teacher has explained all the material but has not used good learning methods, only conventional learning models so that students are active in learning, and are less interested in taking fiqh lessons. This study aims to improve the learning outcomes of grade VI students of MIS Bustanut Tholabah in Fiqh subjects. The location of this research is in class VI MIS Bustanut Tholabah Mekar Jaya Village, Jabung District, East Lampung Regency with a total of 15 students. 7 boys and 8 girls. The data in this study were obtained through interviews, action observation results, and evaluation results. This research was carried out in 3 cycles. The results showed that in cycle I, before the action was taken, the average score was 61.67. The average score increased to 74 after the action. The average score increased to 74 after the action. As for student activity, it was found that 73% of students were active. For the evaluation results, only 60% of students reached the KKM. In cycle II, before the action was taken, the average score was 68.33. The average score increased to 73.66 after the action was taken. The average score increased to 73.66 after the action was taken. As for student activity, 77% of students were found to be active. For evaluation results, 70% of students have reached the KKM. In cycle III, before the action was taken, the average score was 68.33. The average score increased to 85 after the action was taken. Cycle III has achieved success of 80% of students who reached the KKM, and student activity reached 90%. Based on the results of the study it can be concluded that learning with a problem-based learning model can improve student learning outcomes, and increase student activity. Learning becomes more fun because students actively participate in all processes of learning activities, this PBL learning model must support TPACK (TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE) and requires supporting devices that support learning such as projectors, laptops, and at least more fun media. However, this model is less suitable for children who have limitations or disabilities.